CPVL promotes glioma progression via STAT1 pathway inhibition through interactions with the BTK/p300 axis - Hui Yang; Xiaocen Liu; Xiaolong Zhu; Xueqin Li; Lan Jiang; Min Zhong; Mengying Zhang; Tianbing Chen; Mingzhe Ma; Xiuming Liang; Kun Lv (JCI Insight, 2021)
CPVL (carboxypeptidase, vitellogenic-like) is a serine carboxypeptidase that was first characterized in human macrophages. However, the function of CPVL remains unclear in a variety of tumors. The quantitative PCR (qPCR), Western blotting, and IHC assays were utilized to measure the CPVL expression. CPVL was significantly upregulated in glioma cells and tissues compared with normal cells and tissues, respectively. Moreover, high CPVL expression was correlated with advanced clinical grade and poor prognosis. Silencing of CPVL promoted glioma cell apoptosis, and it inhibited cell proliferation and tumorigenicity in vitro and in vivo. Ingenuity Pathway Analysis (IPA) demonstrated that CPVL silencing activated the IFN-γ/STAT1 signaling pathway, thereby inducing glioma cell apoptosis. Mechanistically, immunopurification, mass spectrometry, IP, and glutathione S-transferase (GST) pull-down experiments elucidated that CPVL physically interacts with Bruton’s tyrosine kinase (BTK) and downregulates the STAT1 phosphorylation through promoting p300-mediated STAT1 acetylation. Our findings reveal the crucial role of CPVL in promoting the progression of glioma through suppressing STAT1 phosphorylation. CPVL might serve as a potential prognostic biomarker and therapeutic target for the treatment of glioma.